ANALISIS BAHAN AJAR BAHASA INGGRIS DI SMB DHAMMA PANNA TEMANGGUNG - Dwi Maryati Rispatiningsih; Ayu Lestari (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2020)
This research objectives was to identify and dscribe the quality of English Textboooks. The companion boook entitled English Book Elementary School. Specially, it’s seen from: a) content feasibility; b) language eligibility; c) feasibility of serving; d) Graphic feasibility; and e) the level of readability of the discourse in teaching in teacing materials or text books. This research is evaluative research, the method used in this resarch is mixed methods research. The sbjects of studied were three books. The results showed that the content feasibility, very good category was in KLS 2 and KLS 3, while gor good category in KLS 1. Language eligibility standards, KLS 2 and KLS 3were good categories, KLS 1 had enough categories. In terms of presentation based on the language content, the categories are very good, namely KLS 2 and KLS 3, while for KLS 1 it gets good categoris. In terms of graphics, the categories are very good with the order of KLS 1, KLS 2 and the last is KLS 3 with good categories. The measurement of discourse readability shows that the three English books used in SMB Dhamma Panna Temanggung are not accordance with the class levels taught, especiallly at KLS 1 and KLS 2, while KLS 3 books is better.